2014
DOI: 10.1038/ismej.2014.177
|View full text |Cite
|
Sign up to set email alerts
|

Structural modulation of gut microbiota during alleviation of type 2 diabetes with a Chinese herbal formula

Abstract: The gut microbiota is hypothesized to have a critical role in metabolic diseases, including type 2 diabetes (T2D). A traditional Chinese herbal formula, Gegen Qinlian Decoction (GQD), can alleviate T2D. To find out whether GQD modulates the composition of the gut microbiota during T2D treatment, 187 T2D patients were randomly allocated to receive high (HD, n=44), moderate (MD, n=52), low dose GQD (LD, n=50) or the placebo (n=41) for 12 weeks in a double-blinded trial. Patients who received the HD or MD demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
302
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 372 publications
(320 citation statements)
references
References 54 publications
11
302
0
1
Order By: Relevance
“…In this study, cranberry extract treatment markedly increased the proportion of Akkermansia and decreased intestinal inflammation [97]. Finally, a double-blind trial revealed that changes in the gut microbiota are associated with the glucose-lowering effects of a traditional berberine-containing Chinese herbal formula in type 2 diabetic patients [98]. Indeed, this decoction significantly increased F. prausnitzii, which was negatively correlated with fasting blood glucose, HbA 1c and postprandial blood glucose levels and was positively correlated with HOMA of beta cell function.…”
Section: Dysbiosis Related To Type 2 Diabetes and Hyperglycaemiamentioning
confidence: 89%
“…In this study, cranberry extract treatment markedly increased the proportion of Akkermansia and decreased intestinal inflammation [97]. Finally, a double-blind trial revealed that changes in the gut microbiota are associated with the glucose-lowering effects of a traditional berberine-containing Chinese herbal formula in type 2 diabetic patients [98]. Indeed, this decoction significantly increased F. prausnitzii, which was negatively correlated with fasting blood glucose, HbA 1c and postprandial blood glucose levels and was positively correlated with HOMA of beta cell function.…”
Section: Dysbiosis Related To Type 2 Diabetes and Hyperglycaemiamentioning
confidence: 89%
“…Among the treatments, Chinese Herbal Formulas (TCMs) can serve as valuable therapeutic strategies and drug discovery resources (6). TCMs, which are forms of polypharmacy, have been clinically used in China for treatment of many diseases for thousands of years (7).…”
mentioning
confidence: 99%
“…A higher abundance of Alistipes was also observed in healthy individuals compared to HIV patients treated with antiretroviral therapy or not [35,36]. On the other hand, some studies found Alistipes correlating with health-risk [37][38][39]. Possibly, only in the context of weight-loss, Alistipes indicates a positive constellation.…”
Section: Discussionmentioning
confidence: 95%